2007
DOI: 10.1111/j.1399-0012.2006.00623.x
|View full text |Cite
|
Sign up to set email alerts
|

The fate of recipient‐derived hepatocytes in sex‐mismatched liver allograft following liver transplantation

Abstract: Based on these results, we suggest that ''recipient-specific bone marrow-derived hepatocyte repopulation'' in liver allograft during tissue injury is a relatively early event.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
16
1

Year Published

2008
2008
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 26 publications
1
16
1
Order By: Relevance
“…This finding was confirmed when Ychromosome positive hepatocytes were detected in the livers of female patients who had received bone marrow transplants from male donors (36,(40)(41)(42). The results of these studies broadened the possibility of cell based therapies for the treatment of IMDs of the liver, as the bone marrow would represent a readily available source of liver progenitor cells.…”
Section: Bone Marrow Derived Hepatocytessupporting
confidence: 60%
“…This finding was confirmed when Ychromosome positive hepatocytes were detected in the livers of female patients who had received bone marrow transplants from male donors (36,(40)(41)(42). The results of these studies broadened the possibility of cell based therapies for the treatment of IMDs of the liver, as the bone marrow would represent a readily available source of liver progenitor cells.…”
Section: Bone Marrow Derived Hepatocytessupporting
confidence: 60%
“…This phenomenon was first reported in an aortic allograft model over forty years ago (9, 10) and has been observed to a limited extent when looked for in liver (1117), kidney (18, 19) and heart (20, 21) transplants in human recipients. Fan et al (22) have also recently reported that bone marrow-derived hematopoietic stem cells and progenitor cells infiltrate allogeneic and syngeneic transplants, confirming these findings.…”
Section: Introductionmentioning
confidence: 84%
“…Whereas we and others have demonstrated that there is no or very little involvement of BM-HSC in liver regeneration after OLT [17, 19, 24], other studies reported findings of donor derived hepatocytes in patients that received liver or bone marrow transplants [1416, 22, 23]. The frequency of BM-HSC derived hepatocytes varied between percentages <1% and 8% with some authors using sampling error corrections.…”
Section: Bone Marrow Derived Hematopoietic Stem Cells As Source Fomentioning
confidence: 71%
“…Multiplication of frequency values with these correction factors lead to a reported frequency of BM-HSC derived hepatocytes of up to 43% [15]. Longitudinally performed biopsies suggest that hepatocyte chimerism is an early event (if it occurs at all) which is not correlated with the severity of injury [22, 23]. Several groups examined the status of hepatic cellular chimerism after OLT, reporting that substantial levels of chimerism are commonly found in macrophages, Kupffer cells and endothelial cells of the liver, and bile duct, whereas hepatocyte chimerism was seen only occasionally [18, 20, 21].…”
Section: Bone Marrow Derived Hematopoietic Stem Cells As Source Fomentioning
confidence: 99%